UPAYA PENINGKATAN KUALITAS PELAYANAN APARAT DESA KEPADA PUBLIK - Nur Hidayati (Istithmar: Jurnal Studi Ekonomi Syariah, 2018)
Efforts to improve the quality of service village officials are needed, so that in carrying out the obligations as village officials can be optimal. The phenomenon that occurs there are still officials with a background of junior high education and less optimal in providing services. The research was conducted in Purwoasri village Purwoasri district Kediri, using qualitative research method that is trying to understand certain situation and background as it is, conducting interview with some informant. The result of the research shows that the quality of village officials in providing public services is not good, so it is necessary to improve the quality of service by improving work discipline, mental attitude and behavioral change, and the need for prerequisite standard for educational background for village officials and training service.